Photovoltaic adhesive film and preparation method and application thereof
By using porous magnesium hydroxide carrier to distribute anti-aging additives in the photovoltaic adhesive film, the sustained release of the additives is solved, and the problem of the decrease in the concentration of anti-aging additives in the photovoltaic adhesive film is extended, and the service life of the photovoltaic modules is improved and the stability is improved.
Patent Information
- Application Number
- CN202411675303.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The concentration of anti-aging additives in existing photovoltaic films decreases over time during long-term use, resulting in a decrease in anti-aging performance and affecting the stability and life of photovoltaic modules.
Porous magnesium hydroxide is used as the carrier of anti-aging additives, and the anti-aging additives are distributed through its pores, combined with the natural decomposition of the matrix resin, to achieve sustained release of the anti-aging additives, forming a dynamic balanced anti-aging mechanism.
Effectively maintain the anti-aging performance of photovoltaic films throughout the entire service cycle, avoid accelerated aging caused by additive depletion, significantly extend the service life of photovoltaic modules, and improve long-term power output stability.
Smart Images

Figure CN119505738A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaics, and in particular to a photovoltaic adhesive film and a preparation method and application thereof. Background Art
[0002] Photovoltaic film is an important component of photovoltaic modules and is widely used in various optical products. However, it is found that the concentration of anti-aging additives in the existing photovoltaic film decreases with the extension of service life, resulting in a decrease in the power of photovoltaic modules, which significantly affects the stability and life of photovoltaic modules. Summary of the invention
[0003] The main purpose of the present invention is to provide a photovoltaic adhesive film and its preparation method and application, so as to solve the problem in the prior art that the concentration of anti-aging additives in photovoltaic adhesive films decreases over time during long-term use, resulting in reduced anti-aging performance.
[0004] In order to achieve the above-mentioned purpose, the present invention provides a photovoltaic adhesive film, comprising a base resin and a porous magnesium hydroxide loaded with an anti-aging aid, wherein the anti-aging aid is at least partially distributed in the pores of the porous magnesium hydroxide; the particle size of the porous magnesium hydroxide is 1nm to 100nm; and the porosity of the porous magnesium hydroxide is 20% to 60%.
[0005] Furthermore, the weight ratio of the base resin to the porous magnesium hydroxide loaded with the anti-aging aid is (85-99): (0.0001-15).
[0006] Preferably, the matrix resin is selected from any one or more of EVA, POE, PVB, and silicone.
[0007] Furthermore, the pores of the porous magnesium hydroxide include mesopores, and the volume proportion of the mesopores in the pores is 30% to 80%.
[0008] Preferably, based on 100% of the weight of the porous magnesium hydroxide, the weight of the anti-aging agent in the porous magnesium hydroxide loaded with the anti-aging agent is 20% to 60%.
[0009] Furthermore, the shape of the porous magnesium hydroxide is selected from any one or more of spherical, quasi-spherical, square, and irregular.
[0010] Furthermore, the anti-aging aid is selected from any one or more of an antioxidant, a light stabilizer, and an ultraviolet absorber.
[0011] Preferably, the antioxidant is selected from any one or more of hindered phenol antioxidants, aromatic amine antioxidants, phosphite antioxidants, thioether antioxidants and metal passivator antioxidants.
[0012] Preferably, the light stabilizer is selected from any one or more of a light shielding agent light stabilizer, a quencher light stabilizer, a free radical scavenger light stabilizer and a hydroperoxide decomposer light stabilizer.
[0013] Preferably, the ultraviolet absorber is selected from any one or more of benzophenone compounds and / or benzotriazole compounds.
[0014] Furthermore, the photovoltaic adhesive film also contains fillers.
[0015] Preferably, the filler is selected from any one or more of calcium carbonate, barium sulfate, talc, titanium dioxide, zinc oxide, carbon black, graphene, graphene oxide, copper chrome black, magnesium hydroxide, aluminum hydroxide, aluminum oxide, magnesium oxide, boron nitride, silicon carbide, ammonium phosphate, and ammonium polyphosphate.
[0016] Furthermore, the photovoltaic adhesive film also contains any one or more of a cross-linking agent, a co-cross-linking agent, and a tackifier.
[0017] Preferably, the crosslinking agent is selected from any one or more of tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-amyl peroxy 2-ethylhexyl carbonate, 2,5-dimethyl 2,5-dimethyl 2,5-dimethyl 2,5-bis(benzoylperoxy)-hexane, tert-amyl peroxy carbonate, and tert-butyl peroxy 3,3,5-trimethylhexanoate.
[0018] Preferably, the auxiliary crosslinking agent is selected from triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane tetraacrylate. Any one or more of acrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, 2,4,6-tris(2-propenyloxy)-1,3,5-triazine, tricyclodecane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate and polyethylene glycol dimethacrylate.
[0019] Preferably, the tackifier is selected from any one or more of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethylsilane, and 3-aminopropyltrimethylsilane.
[0020] Furthermore, the thickness of the photovoltaic film ranges from 0.1 mm to 0.6 mm.
[0021] Furthermore, the porous magnesium hydroxide loaded with the anti-aging agent is prepared by a wet impregnation method.
[0022] Preferably, the porous magnesium hydroxide is immersed in a solution of an anti-aging agent to obtain porous magnesium hydroxide loaded with an anti-aging agent, and the solvent of the solution of the anti-aging agent is selected from any one or more of methanol, ethanol, acetone, ethyl acetate, dichloromethane, and N,N-dimethylformamide.
[0023] More preferably, in the solution of the anti-aging agent, the concentration of the anti-aging agent is 0.18 mol / L to 3.60 mol / L, and the immersion treatment time is 0.5 h to 2 h.
[0024] More preferably, the porous magnesium hydroxide is immersed in a solution of the anti-aging agent and then dried at 45° C. to 65° C. for 2 h to 6 h to obtain the porous magnesium hydroxide loaded with the anti-aging agent.
[0025] The preparation method of the photovoltaic adhesive film as described above comprises the following steps: mixing the base resin and the porous magnesium hydroxide loaded with the anti-aging agent according to the composition of the photovoltaic adhesive film to obtain a mixture, and extruding and casting the mixture into a film to obtain the photovoltaic adhesive film.
[0026] Preferably, the temperature of the extrusion casting is 90°C to 120°C.
[0027] According to another aspect of the present invention, a photovoltaic module is provided, which includes a panel, a first adhesive film, a battery cell, a second adhesive film and a backplane stacked in sequence, the first adhesive film and / or the second adhesive film is the photovoltaic adhesive film as described above, or the first adhesive film and / or the second adhesive film is a photovoltaic adhesive film prepared by the preparation method as described above.
[0028] The technical scheme of the present invention is applied, and porous magnesium hydroxide is used as a carrier of an anti-aging aid. This carrier material has a pore structure, and the anti-aging aid can be effectively accommodated and protected. When the photovoltaic film ages under natural conditions, for example, when affected by environmental factors such as ultraviolet rays, high temperature, and moisture, matrix resins such as EVA, additives, backboards, etc. will gradually decompose to produce free acids (such as acetic acid, silicic acid, etc.), and the free acids produced by these decompositions and the free acids penetrated by the outside world will corrode the structure of porous magnesium hydroxide, and the corrosion of magnesium hydroxide can both neutralize the free acids and simultaneously promote the anti-aging aid to be slowly released, and the released additives play their own anti-aging functions, such as anti-acid effect, light stabilization, antioxidant effect, etc., so as to form a dynamic balance anti-aging mechanism, and this mechanism can ensure that the anti-aging performance of the photovoltaic film is maintained at a relatively stable level throughout the use cycle. Through the slow release of the anti-aging aid, the photovoltaic module can maintain a higher anti-aging performance throughout the use cycle, avoiding the phenomenon that the traditional film is accelerated aging due to the exhaustion of the additive in the later stage, thereby significantly extending the service life of the photovoltaic module. In addition, by neutralizing the free acid generated by the decomposition of the matrix resin, etc., it helps to inhibit the aggravation of the PID (potentially induced degradation) effect and improve the long-term power output stability of the photovoltaic module. Furthermore, in the prior art, in the initial stage after the photovoltaic film is just prepared, the concentration of the anti-aging agent is the maximum, and then gradually decreases with the increase of service life. In the initial stage of anti-aging, such a large dose of anti-aging agent is not required. The slow-release mechanism reduces the excessive use of anti-aging agents during the production of photovoltaic films, reduces the potential impact of anti-aging agents on the environment, and improves the environmental protection of photovoltaic modules. At the same time, due to the improved use efficiency of the anti-aging agent, the initial addition amount of the anti-aging agent is reduced, thereby reducing the production cost.
[0029] By adopting the photovoltaic adhesive film of the present invention, free acid generated by decomposition of the base resin and free acid infiltrated from the outside are neutralized while corroding magnesium hydroxide, and anti-aging additives such as light stabilizers and antioxidants coated therein are released while the magnesium hydroxide is corroded. The release rate of the anti-aging additives matches the natural decomposition rate of the base resin, achieving a long-term virtuous cycle, solving the problem of decreased anti-aging performance of traditional photovoltaic adhesive films during long-term use, improving the service life and performance stability of photovoltaic modules, and controlling production costs at the same time, having significant technical advantages and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0031] Figure 1 The hydrothermal corrosion of the photovoltaic module prepared by the photovoltaic adhesive film in Example 1 at different times is shown; wherein, from left to right, the hydrothermal corrosion after 0h, 500h, 1000h, 1500h, and 2000h of wet heat aging are shown; and
[0032] Figure 2 The hydrothermal corrosion conditions of the photovoltaic modules prepared by the photovoltaic film in Comparative Example 1 at different times are shown; among them, from left to right are the hydrothermal corrosion conditions after 0h, 500h, 1000h, 1500h, and 2000h of wet heat aging. DETAILED DESCRIPTION
[0033] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0034] As described in the background art, the prior art has the problem that the concentration of the anti-aging agent of the photovoltaic film decreases over time during long-term use, resulting in reduced anti-aging performance. In order to solve the above problem, the present invention provides a photovoltaic film, including a base resin and porous magnesium hydroxide loaded with an anti-aging agent, wherein the anti-aging agent is at least partially distributed in the pores of the porous magnesium hydroxide; the particle size of the porous magnesium hydroxide is 1nm to 100nm; and the porosity of the porous magnesium hydroxide is 20% to 60%.
[0035] Based on the photovoltaic adhesive film provided by the present invention, porous magnesium hydroxide is used as the carrier of the anti-aging auxiliary agent, and this carrier material has a pore structure, which can effectively accommodate and protect the anti-aging auxiliary agent. When the photovoltaic adhesive film ages under natural conditions, for example, when affected by environmental factors such as ultraviolet rays, high temperature, and moisture, the matrix resins such as EVA, auxiliary agents, backboards themselves, etc. will gradually decompose, and free acids (such as acetic acid, silicic acid, etc.) will be produced. The free acids produced by these decompositions and the free acids penetrated by the outside world will corrode the structure of porous magnesium hydroxide, and the corrosion of magnesium hydroxide can both neutralize the free acids and simultaneously promote the anti-aging auxiliary agent to be slowly released, and the released auxiliary agent plays its own anti-aging function, such as anti-acid effect, light stabilization, antioxidant effect, etc., so as to form a dynamic balance anti-aging mechanism, and this mechanism can ensure that the anti-aging performance of the photovoltaic adhesive film is maintained at a relatively stable level throughout the use cycle. Through the slow release of the anti-aging auxiliary agent, the photovoltaic module can maintain a higher anti-aging performance throughout the use cycle, avoiding the phenomenon that the traditional adhesive film is accelerated aging due to the exhaustion of auxiliary agents in the later stage, thereby significantly extending the service life of the photovoltaic module. In addition, by neutralizing the free acid of the acid radical ions generated by the decomposition of the matrix resin, it helps to suppress the aggravation of the PID (potentially induced degradation) effect, thereby improving the long-term power output stability of the photovoltaic module. Furthermore, in the prior art, in the initial stage after the photovoltaic film is just prepared, the concentration of the anti-aging agent is at the maximum value, and then gradually decreases with the increase of service life. In the initial stage of anti-aging, such a large dose of anti-aging agent is not required. The slow-release mechanism reduces the excessive use of anti-aging agents during the production of photovoltaic films, reduces the potential impact of anti-aging agents on the environment, and improves the environmental protection of photovoltaic modules. At the same time, due to the improved use efficiency of the anti-aging agent, the initial addition amount of the anti-aging agent is reduced, thereby reducing the production cost. By adopting the photovoltaic adhesive film of the present invention, the free acid of organic acid generated by the decomposition of the base resin and the free acid infiltrated from the outside corrode the magnesium hydroxide and are neutralized at the same time. When the magnesium hydroxide is corroded, the light stabilizer, antioxidant and other anti-aging additives coated therein are released. The release rate of the anti-aging additive matches the natural decomposition rate of the base resin, achieving a long-term virtuous cycle, solving the problem of the decline in the anti-aging performance of traditional photovoltaic adhesive films during long-term use, improving the service life and performance stability of photovoltaic modules, and controlling the production cost at the same time. It has significant technical advantages and application prospects.
[0036] In addition, the particle size of porous magnesium hydroxide is 1nm to 100nm. Nano-scale porous magnesium hydroxide has a high specific surface area and a large pore volume. Under the same weight, nanomaterials can provide more pore space to load anti-aging additives, and the nanomaterials have a small particle size and can be more easily dispersed in the matrix resin, thereby improving the uniformity of the distribution of the anti-aging additives and the performance consistency of the overall photovoltaic film; the porosity of porous magnesium hydroxide is 20% to 60%. For porous magnesium hydroxide, the porosity directly affects the stability of its pore structure, the connectivity of the pores, and the loading and release capacity of the anti-aging additive. The porosity is within the above range, which can not only effectively encapsulate the anti-aging additive to ensure the sustained release efficiency and anti-aging effect, but also ensure the connectivity and mechanical strength of the pore structure, which is convenient for the sustained release of the additive, and at the same time has excellent processing performance to avoid breakage during processing.
[0037] In some embodiments, the weight ratio of the base resin and the porous magnesium hydroxide loaded with the anti-aging agent is (85-99): (0.0001-15). Under the above weight ratio, both a higher base resin strength can be obtained and sufficient anti-aging agent loading in the photovoltaic film can be achieved to obtain a higher anti-aging effect; preferably, the base resin is selected from any one or more of EVA, POE, PVB, and silicone, which are commonly used in photovoltaic module packaging and have good transparency, adhesion and weather resistance. Especially EVA and silicone, because they release organic acids (such as acetic acid and silicic acid) when they decompose naturally, these acidic substances can react with the magnesium hydroxide in the porous magnesium hydroxide, thereby promoting the slow release of the anti-aging agent. The pore structure of the porous magnesium hydroxide provides a stable hiding place for the anti-aging agent, and the acidic environment generated by the natural decomposition of these base resins can serve as a trigger mechanism for the slow release of the agent.
[0038] In some embodiments, the pores of porous magnesium hydroxide include mesopores, and the volume proportion of mesopores in the pores is 30% to 80%. Mesoporous materials (pore size between 2 and 50 nm) have attracted widespread attention due to their unique pore structure, especially in the fields of catalysts, adsorbents and drug sustained release. Mesoporous porous magnesium hydroxide is introduced into photovoltaic adhesive films as a carrier of anti-aging additives. The presence of a large number of mesopores provides a large number of evenly distributed pores, which not only increases the anti-aging additive loading capacity of the magnesium hydroxide carrier, but also ensures the uniform distribution of the anti-aging additive. In addition, the pore size and porosity of the mesopores have become key factors in limiting the excessive release of the additive, and can effectively control the release rate of the additive. This control mechanism helps to avoid the premature exhaustion of the additive during the initial aging of the matrix resin, and ensures that the additive can be released at an appropriate rate throughout the entire service life of the photovoltaic adhesive film to meet the needs of different aging stages. The pore structure of the porous magnesium hydroxide is designed to contain the above-mentioned proportion of mesoporous materials, which helps to encapsulate sufficient anti-aging additives to ensure the anti-aging effect, better control the release rate of the additives to obtain a higher service life and performance stability, and at the same time have higher mechanical strength.
[0039] In some preferred embodiments, the weight of the porous magnesium hydroxide loaded with the anti-aging agent is 20% to 60%, based on the weight of the porous magnesium hydroxide as 100%. Porous magnesium hydroxide, especially mesoporous materials, has high porosity and large specific surface area, and can effectively adsorb and encapsulate the anti-aging agent. When the weight proportion of the anti-aging agent is adjusted to 20% to 60%, the pores of the mesoporous magnesium hydroxide are fully and evenly filled with the anti-aging agent so that the photovoltaic module can maintain a high anti-aging performance throughout the entire service life, and the initial addition amount of the anti-aging agent is small, which reduces the cost and improves environmental protection.
[0040] In some embodiments, the shape of the porous magnesium hydroxide is selected from any one or more of spherical, quasi-spherical, square, and irregular. The shape of the porous magnesium hydroxide is preferably spherical. The spherical or quasi-spherical porous magnesium hydroxide has a low friction coefficient and high fluidity, so as to be evenly mixed with the matrix resin during the mixing process, improve the processing performance of the casting process, reduce defects in the processing process, and improve the production efficiency and quality of the film.
[0041] In some specific embodiments, the porous magnesium hydroxide carrier can be commercially available, or prepared by hydrothermal synthesis, sol-gel method or precipitation method.
[0042] In some embodiments, the anti-aging additive is selected from any one or more of an antioxidant, a light stabilizer, and an ultraviolet absorber. In a long-term outdoor use environment, the photovoltaic film will be affected by multiple factors such as ultraviolet rays, high temperature, humidity, and oxidation, resulting in a decrease in its performance, thereby affecting the efficiency and life of the photovoltaic module. The selection of these additives, combined with the slow-release properties of porous magnesium hydroxide, can specifically resist the aging process of the photovoltaic film and extend its service life.
[0043] Antioxidants are used to improve the stability of polymers during extrusion processing, as well as during long-term use, and to delay degradation due to the action of heat and oxygen. In some embodiments, the antioxidant is selected from any one or more of hindered phenol antioxidants, aromatic amine antioxidants, phosphite antioxidants, thioether antioxidants, and metal deactivator antioxidants; preferably, the antioxidant is a hindered phenol compound and / or a phosphite compound. Compared with other antioxidants, the above antioxidants have better stability and antioxidant properties. Specifically, hindered phenol compounds include but are not limited to 2,6-di-tert-butyl-4-ethylphenol, 2,2'-methylene-bis-(4-methyl-6-tert-butylphenol), 2,2'-methylene-bis-(4-ethyl-6-tert-butylphenol), 4,4'-butylene-bis-(3-methyl-6-tert-butylphenol), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-1,2-di-tert-butyl-6-tert-butylphenol, ... The phosphite-based compounds include, but are not limited to, one or more of tris(2,4-di-tert-butylphenyl)phosphite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl ester phosphite, tetrakis(2,4-di-tert-butylphenyl)[1,1-phenylene]-4,4'-diyl bisphosphite and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.
[0044] Light stabilizers are used to improve the stability of encapsulant films or liquid encapsulants under long-term ultraviolet radiation. In some embodiments, the light stabilizer is selected from any one or more of light-shielding agent-type light stabilizers, quencher-type light stabilizers, free radical scavenger-type light stabilizers and hydroperoxide decomposer-type light stabilizers; preferably, the light stabilizer is a hindered amine compound, specifically, including but not limited to bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, a graft copolymer obtained by polymerization of 4-(methyl)acryloyloxy-2,2,6,6-tetramethylpiperidine and α-olefin monomers, 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, 3,5-di-tert-butyl-4-hydroxy-benzoic acid hexadecyl ester, sebacate bis-2,2,6,6-tetramethylpiperidinol and tris(1,2,2,6,6-pentamethyl-4-piperidinyl) phosphite.
[0045] Ultraviolet light absorbers refer to substances that can absorb most of the ultraviolet energy and convert it into heat, thereby protecting certain electronic devices from being damaged by ultraviolet rays. In some embodiments, the ultraviolet light absorbers are selected from benzophenone compounds and / or benzotriazole compounds; specifically, the ultraviolet light absorbers include but are not limited to any one or more of 2-hydroxy-4-n-octyloxybenzophenone, 2,2-tetramethylenebis(3,1-benzoxazine-4-one), 2-(2'-hydroxy-5-methylphenyl)benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, phenyl o-hydroxybenzoate, 2,4-dihydroxybenzophenone and 2-hydroxy-4-methoxybenzophenone.
[0046] In some embodiments, the photovoltaic film further contains fillers. The fillers can improve the physical and chemical properties of the photovoltaic film by filling the microscopic gaps in the film matrix, and enhance the mechanical strength, heat resistance, moisture resistance and barrier properties of the photovoltaic film. In addition, some fillers also have a light scattering effect, which can reduce the direct penetration of ultraviolet rays and indirectly improve the light stability of the film.
[0047] In some preferred embodiments, the filler is selected from any one or more of calcium carbonate, barium sulfate, talc, titanium dioxide, zinc oxide, carbon black, graphene, graphene oxide, copper chrome black, magnesium hydroxide, aluminum hydroxide, aluminum oxide, magnesium oxide, boron nitride, whisker silicon carbide, ammonium phosphate, and ammonium polyphosphate; more preferably, the filler is selected from any one or more of calcium carbonate, talc and whisker silicon carbide.
[0048] In some embodiments, the photovoltaic adhesive film further contains any one or more of a cross-linking agent, a co-cross-linking agent, and a tackifier.
[0049] Crosslinking agents are used to induce chemical crosslinking between polymer molecules to form a more stable three-dimensional network structure. In photovoltaic adhesive films, the use of crosslinking agents can improve the thermal stability and chemical resistance of photovoltaic adhesive films, reduce deformation and degradation in high temperature or hot and humid environments, and enhance the bonding strength between the adhesive film and other parts of the photovoltaic module. The crosslinking agent can be selected from commonly used types in the field. In some preferred embodiments, the crosslinking agent is selected from tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-amyl peroxy 2-ethylhexyl carbonate, 2,5-dimethyl 2,5-dimethyl 2,5-dimethyl 2,5-bis(benzoylperoxy)-hexane, tert-amyl peroxy carbonate, and any one or more of peroxidized 3,3,5-trimethyl tert-butyl hexanoate.
[0050] The addition of a tackifier is beneficial to improving the bonding performance between the adhesive film and the substrate. In some preferred embodiments, the auxiliary crosslinking agent is selected from triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylol Any one or more of propane tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, 2,4,6-tris(2-propenyloxy)-1,3,5-triazine, tricyclopentane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate and polyethylene glycol dimethacrylate.
[0051] The addition of a tackifier is beneficial to improving the bonding performance between the adhesive film and the substrate. In some preferred embodiments, the tackifier is selected from any one or more of γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, vinyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, γ-glycidyloxypropyl trimethylsilane, and 3-aminopropyl trimethylsilane.
[0052] In some embodiments, the thickness of the photovoltaic adhesive film ranges from 0.1 mm to 0.6 mm. As a key material for interlayer packaging in photovoltaic modules, the thickness of the photovoltaic adhesive film has a direct impact on the packaging quality, optical properties and weather resistance of the module. Within this thickness range, while ensuring sufficient bonding strength, it has better light transmittance, flexibility and mechanical strength.
[0053] In some embodiments, the porous magnesium hydroxide loaded with the anti-aging agent is prepared by wet impregnation.
[0054] Preferably, porous magnesium hydroxide is placed in a solution of an anti-aging aid and soaked to obtain porous magnesium hydroxide loaded with an anti-aging aid, and the solvent of the solution of the anti-aging aid is selected from any one or more of methanol, ethanol, acetone, ethyl acetate, dichloromethane, and N,N-dimethylformamide. Porous magnesium hydroxide is placed in a solution of an anti-aging aid, and the anti-aging aid molecules enter the pores of porous magnesium hydroxide through physical adsorption, capillary action, and intermolecular interaction. In this process, the anti-aging aid molecules in the solution will be attracted by the pore structure of the porous material, gradually penetrate and fill the pores until saturation or a preset load level is reached, and the process is simple and easy to operate.
[0055] More preferably, in order to ensure that the anti-aging agent molecules can penetrate deeply into the pores and increase the loading amount, auxiliary means such as ultrasound, heating, and vacuum can be used during the impregnation process to promote the diffusion and adsorption of the anti-aging agent molecules.
[0056] More preferably, in the solution of the anti-aging agent, the concentration of the anti-aging agent is 0.18 mol / L to 3.60 mol / L, and the immersion treatment time is 0.5 h to 2 h, so as to achieve efficient loading and high loading amount of the anti-aging agent, and to achieve uniform distribution of the agent molecules in the porous magnesium hydroxide, so that during the service life of the photovoltaic module, the anti-aging agent can be evenly and slowly released to extend the service life of the module.
[0057] More preferably, the porous magnesium hydroxide is immersed in a solution of an anti-aging agent and then dried at 45°C to 65°C for 2h to 6h to obtain a porous magnesium hydroxide loaded with an anti-aging agent. The porous magnesium hydroxide impregnated with the anti-aging agent is dried to remove the solvent, thereby improving the thermal stability and chemical stability of the porous magnesium hydroxide loaded with the anti-aging agent, avoiding the loss of the anti-aging agent in the subsequent granulation and mixing process, ensuring the long-term effectiveness of the anti-aging agent, enhancing its anti-aging performance during the use of photovoltaic modules, and extending the service life of the modules.
[0058] According to another aspect of the present invention, a method for preparing the above photovoltaic adhesive film is provided, comprising the following steps: mixing a matrix resin and a porous magnesium hydroxide loaded with an anti-aging agent according to the composition of the photovoltaic adhesive film to obtain a mixture, and extruding and casting the mixture into a film to obtain a photovoltaic adhesive film. The porous magnesium hydroxide loaded with an anti-aging agent and the matrix resin are heated to a molten state, and then a continuous and uniform photovoltaic adhesive film is formed by casting and extrusion, and the process is simple.
[0059] Preferably, the temperature of extrusion casting is 90°C to 120°C. Within this temperature range, matrix resins such as EVA can be fully melted and have good fluidity, which is convenient for subsequent casting extrusion operations and helps to avoid the risk of decomposition of anti-aging agents and damage to the structure of porous materials, and better maintain the activity of anti-aging agents and the integrity of the pore structure of porous materials, thereby obtaining a uniform, high-quality photovoltaic adhesive film and improving the packaging quality of photovoltaic modules.
[0060] According to another aspect of the present invention, a photovoltaic module is provided, which includes a panel, a first adhesive film, a battery cell, a second adhesive film and a backboard stacked in sequence, the first adhesive film and / or the second adhesive film is the photovoltaic adhesive film as described above, or the first adhesive film and / or the second adhesive film is a photovoltaic adhesive film prepared by the preparation method as described above.
[0061] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0062] Unless otherwise specified, the raw materials and reagents used in the examples and comparative examples were purchased from the market.
[0063] Example 1
[0064] A photovoltaic adhesive film, comprising a matrix resin EVA and porous magnesium hydroxide loaded with an anti-aging aid, wherein the anti-aging aid is at least partially distributed in the pores of the porous magnesium hydroxide;
[0065] The porous magnesium hydroxide is spherical, the particle size of the porous magnesium hydroxide is 50 nm, the porosity of the porous magnesium hydroxide is 52%, the pores of the porous magnesium hydroxide include mesopores, and the volume proportion of the mesopores in the pores is 60%; based on the weight of the porous magnesium hydroxide being 100%, the weight of the anti-aging agent in the porous magnesium hydroxide loaded with the anti-aging agent is 50%;
[0066] The weight ratio of the base resin to the porous magnesium hydroxide loaded with the anti-aging additive is 92:0.5;
[0067] The porous magnesium hydroxide loaded with an anti-aging aid is obtained by the following steps:
[0068] The porous magnesium hydroxide is immersed in a solution of an anti-aging agent, and then dried at 50°C for 4 hours to obtain the porous magnesium hydroxide loaded with the anti-aging agent; wherein the solvent of the solution of the anti-aging agent is ethanol; in the solution of the anti-aging agent, the anti-aging agent consists of an antioxidant 2,6-di-tert-butyl-4-ethylphenol, a light stabilizer bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacic acid ester, and an ultraviolet absorber 2-(2'-hydroxy-5-methylphenyl) benzotriazole, and the concentrations thereof are 1.2 mol / L, 1.2 mol / L, and 1.2 mol / L, respectively, and the immersion treatment time is 1 hour.
[0069] The steps for preparing photovoltaic film are as follows:
[0070] The matrix resin, auxiliary additives, and porous magnesium hydroxide loaded with anti-aging additives are formulated according to the composition of the photovoltaic film and mixed to obtain a mixture, and the mixture is extruded and cast into a film at 100° C. to obtain a photovoltaic film with a thickness of 0.4 mm.
[0071] Example 2
[0072] A photovoltaic adhesive film comprises a base resin and porous magnesium hydroxide loaded with an anti-aging agent, wherein the anti-aging agent is at least partially distributed in the pores of the porous magnesium hydroxide;
[0073] The porous magnesium hydroxide is spherical, the particle size of the porous magnesium hydroxide is 1 nm, and the porosity of the porous magnesium hydroxide is 20%. Taking the weight of the porous magnesium hydroxide as 100%, the weight of the anti-aging agent in the porous magnesium hydroxide loaded with the anti-aging agent is 20%.
[0074] The weight ratio of the base resin to the porous magnesium hydroxide loaded with the anti-aging additive is 85:15;
[0075] The porous magnesium hydroxide loaded with an anti-aging aid is obtained by the following steps:
[0076] The porous magnesium hydroxide is immersed in a solution of an anti-aging agent, and then dried at 50°C for 4 hours to obtain the porous magnesium hydroxide loaded with the anti-aging agent; wherein the solvent of the solution of the anti-aging agent is ethanol; in the solution of the anti-aging agent, the anti-aging agent consists of an antioxidant 2,6-di-tert-butyl-4-ethylphenol and a light stabilizer bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacic acid ester, and their concentrations are 1 mol / L respectively, and the immersion treatment time is 1 hour.
[0077] The steps for preparing photovoltaic film are as follows:
[0078] The matrix resin, auxiliary additives, and porous magnesium hydroxide loaded with anti-aging additives are formulated according to the composition of the photovoltaic film and mixed to obtain a mixture, and the mixture is extruded and cast into a film at 100° C. to obtain a photovoltaic film with a thickness of 0.2 mm.
[0079] Example 3
[0080] A photovoltaic adhesive film comprises a base resin and porous magnesium hydroxide loaded with an anti-aging agent, wherein the anti-aging agent is at least partially distributed in the pores of the porous magnesium hydroxide;
[0081] The porous magnesium hydroxide is spherical, the particle size of the porous magnesium hydroxide is 100 nm, the porosity of the porous magnesium hydroxide is 60%, the pores of the porous magnesium hydroxide include mesopores, and the volume proportion of the mesopores in the pores is 80%; based on the weight of the porous magnesium hydroxide being 100%, the weight of the anti-aging agent in the porous magnesium hydroxide loaded with the anti-aging agent is 60%;
[0082] The weight ratio of the base resin and the porous magnesium hydroxide loaded with the anti-aging additive is 99:0.0001;
[0083] The porous magnesium hydroxide loaded with an anti-aging aid is obtained by the following steps:
[0084] The porous magnesium hydroxide is immersed in a solution of an anti-aging agent, and then dried at 50°C for 4 hours to obtain porous magnesium hydroxide loaded with an anti-aging agent; wherein the solvent of the solution of the anti-aging agent is ethanol; in the solution of the anti-aging agent, the anti-aging agent is an antioxidant 2,6-di-tert-butyl-4-ethylphenol, the concentration of which is 0.18 mol / L, and the immersion time is 1 hour.
[0085] The steps for preparing photovoltaic film are as follows:
[0086] The matrix resin and the porous magnesium hydroxide loaded with the anti-aging additive are formulated according to the composition of the photovoltaic film and mixed to obtain a mixture, and the mixture is extruded and cast into a film at 100° C. to obtain a photovoltaic film with a thickness of 0.6 mm.
[0087] Example 4
[0088] The only difference between it and Example 1 is that the particle size of the porous magnesium hydroxide is 100 nm.
[0089] Example 5
[0090] The only difference between it and Example 1 is that the porosity of the porous magnesium hydroxide is 20%.
[0091] Example 6
[0092] The only difference between it and Example 1 is that the porosity of the porous magnesium hydroxide is 60%.
[0093] Example 7
[0094] The only difference between it and Example 1 is that, in the porous magnesium hydroxide, the volume of the mesopores in the pores accounts for 30%.
[0095] Example 8
[0096] The only difference between it and Example 1 is that in the porous magnesium hydroxide, the volume of the mesopores in the pores accounts for 80%.
[0097] Example 9
[0098] The only difference between it and Example 1 is that, in the porous magnesium hydroxide, the volume proportion of mesopores in the pores is 20%.
[0099] Example 10
[0100] The only difference between it and Example 1 is that, in the porous magnesium hydroxide, the weight ratio of the base resin to the porous magnesium hydroxide loaded with the anti-aging additive is 85:15.
[0101] Embodiment 11
[0102] The only difference between it and Example 1 is that the weight ratio of the base resin and the porous magnesium hydroxide loaded with the anti-aging additive is 99:0.0001.
[0103] Example 12
[0104] The only difference between it and Example 1 is that the weight ratio of the base resin and the porous magnesium hydroxide loaded with the anti-aging additive is 85:20.
[0105] Comparative Example 1
[0106] The only difference between the embodiment 1 and the embodiment 1 is that the porous magnesium hydroxide loaded with the anti-aging aid is not added.
[0107] Comparative Example 2
[0108] A photovoltaic adhesive film, comprising a matrix resin EVA grease, an anti-aging additive and porous magnesium hydroxide;
[0109] Among them, the porous magnesium hydroxide is spherical, the particle size of the porous magnesium hydroxide is 50nm, the porosity of the porous magnesium hydroxide is 52%, the pores of the porous magnesium hydroxide include mesopores, and the volume proportion of the mesopores in the pores is 60%; the weight ratio of the base resin, the anti-aging additive, and the porous magnesium hydroxide is 92:0.25:0.25; among them, the anti-aging additive is composed of the antioxidant 2,6-di-tert-butyl-4-ethylphenol, the light stabilizer bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacic acid ester and the ultraviolet absorber 2-(2'-hydroxy-5-methylphenyl) benzotriazole in a mass ratio of 1:1:1.
[0110] The steps for preparing photovoltaic film are as follows:
[0111] The base resin, anti-aging additive and porous magnesium hydroxide are formulated according to the composition of the photovoltaic film and mixed to obtain a mixture, and the mixture is extruded and cast at 100° C. to form a film to obtain a photovoltaic film, and the thickness of the photovoltaic film is 0.4 mm.
[0112] Comparative Example 3
[0113] The only difference between it and Example 1 is that the particle size of the porous magnesium hydroxide is 150 nm.
[0114] Comparative Example 4
[0115] The only difference between it and Example 1 is that the porosity of the porous magnesium hydroxide is 10%.
[0116] Comparative Example 5
[0117] The only difference between it and Example 1 is that the porosity of the porous magnesium hydroxide is 80%.
[0118] 1. Preparation of finished photovoltaic modules:
[0119] The photovoltaic adhesive films prepared in Examples 1-6 and Comparative Examples 1-4 were used to prepare photovoltaic modules respectively, and the specific steps were as follows:
[0120] The tempered glass, the prepared photovoltaic film, the battery cell (Tongwei), the prepared photovoltaic film and the backplane are stacked in this order, and the bubbles are removed by evacuating at 165°C (the vacuum gauge pressure is -0.99atm). After curing for 18 minutes, a photovoltaic module can be obtained.
[0121] 2. Performance Test
[0122] (1) Peel strength test: According to GB / T 2790-1995, the peel strength between the adhesive film and the glass in the photovoltaic module prepared above was measured to obtain the peel strength before aging. The results are shown in Table 1.
[0123] (2) Aging performance test: The photovoltaic modules prepared above were placed in an aging box at a temperature of 120° C. and a humidity of 100%. After 48 hours, the peel strength was tested to obtain the peel strength after aging. The results are shown in Table 1.
[0124] (3) Yellowing value test: Use a spectrophotometer to test the yellowness index (YI) of the photovoltaic module before and after aging in step (2), and the yellowing value before and after aging ΔYI = YI after aging - YI before aging; wherein, the test conditions adopt a reflectivity measurement mode including specular reflection, and a trace amount of ultraviolet light is included in the measurement light source.
[0125] (4) Hygrothermal aging (DH) - electroluminescence (EL) test: The PV modules prepared as above were subjected to an electroluminescence (EL) tester to take initial EL photos, and then placed in a DH aging chamber (temperature of 85°C, humidity of 85% Rh). EL photos were taken every 500 h for a total of 2000 h. The hydrothermal corrosion of the PV modules was determined by observing the photos.
[0126] Table 1
[0127]
[0128]
[0129] As shown in Table 1, compared with Comparative Examples 1-4, the photovoltaic adhesive films prepared in Examples 1-12 have higher peel strength after aging, and lower yellowing values before and after aging, and have excellent anti-aging and anti-yellowing properties, which can improve the service life and performance stability of photovoltaic modules. Figure 1 and Figure 2 It can be seen that, compared with the photovoltaic film in Comparative Example 1, the photovoltaic module prepared based on the photovoltaic film in Example 1 of the present invention has more excellent water-heat corrosion resistance.
[0130] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A photovoltaic film, characterized in that: The porous magnesium hydroxide comprises a matrix resin and a loaded anti-aging aid, wherein the anti-aging aid is at least partially distributed in the pores of the porous magnesium hydroxide; the particle size of the porous magnesium hydroxide is 1nm-100nm; and the porosity of the porous magnesium hydroxide is 20%-60%.
2. The photovoltaic adhesive film according to claim 1, characterized in that: The weight ratio of the base resin to the porous magnesium hydroxide loaded with the anti-aging aid is (85-99): (0.0001-15); Preferably, the matrix resin is selected from any one or more of EVA, POE, PVB, and silicone.
3. The photovoltaic adhesive film according to claim 1, characterized in that: The pores of the porous magnesium hydroxide include mesopores, and the volume proportion of the mesopores in the pores is 30% to 80%; Preferably, based on 100% of the weight of the porous magnesium hydroxide, the weight of the anti-aging aid in the porous magnesium hydroxide loaded with the anti-aging aid is 20% to 60%.
4. The photovoltaic adhesive film according to any one of claims 1 to 3, characterized in that: The shape of the porous magnesium hydroxide is selected from any one or more of spherical, quasi-spherical, square, and irregular.
5. The photovoltaic adhesive film according to any one of claims 1 to 3, characterized in that: The anti-aging aid is selected from any one or more of an antioxidant, a light stabilizer, and a UV absorber; Preferably, the antioxidant is selected from any one or more of hindered phenol antioxidants, aromatic amine antioxidants, phosphite antioxidants, thioether antioxidants and metal passivator antioxidants; Preferably, the light stabilizer is selected from any one or more of a light shielding agent light stabilizer, a quencher light stabilizer, a free radical scavenger light stabilizer and a hydroperoxide decomposer light stabilizer; Preferably, the ultraviolet absorber is selected from any one or more of benzophenone compounds and / or benzotriazole compounds.
6. The photovoltaic adhesive film according to any one of claims 1 to 3, characterized in that: The photovoltaic adhesive film further contains fillers; and / or, The photovoltaic adhesive film further contains any one or more of a cross-linking agent, a co-cross-linking agent, and a tackifier; Preferably, the filler is selected from any one or more of calcium carbonate, barium sulfate, talc, titanium dioxide, zinc oxide, carbon black, graphene, graphene oxide, copper chrome black, magnesium hydroxide, aluminum hydroxide, aluminum oxide, magnesium oxide, boron nitride, silicon carbide, ammonium phosphate, and ammonium polyphosphate; Preferably, the cross-linking agent is selected from any one or more of tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-amyl peroxy 2-ethylhexyl carbonate, 2,5-dimethyl 2,5-dimethyl 2,5-dimethyl 2,5-bis(benzoylperoxy)-hexane, tert-amyl peroxy carbonate, and tert-butyl peroxy 3,3,5-trimethylhexanoate; Preferably, the auxiliary crosslinking agent is selected from triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane Any one or more of tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, 2,4,6-tris(2-propenyloxy)-1,3,5-triazine, tricyclohexane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate and polyethylene glycol dimethacrylate; Preferably, the tackifier is selected from any one or more of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethylsilane, and 3-aminopropyltrimethylsilane.
7. The photovoltaic adhesive film according to any one of claims 1 to 3, characterized in that: The thickness of the photovoltaic adhesive film ranges from 0.1 mm to 0.6 mm.
8. The photovoltaic adhesive film according to any one of claims 1 to 3, characterized in that: The porous magnesium hydroxide loaded with the anti-aging additive is prepared by wet impregnation; Preferably, the porous magnesium hydroxide is immersed in a solution of an anti-aging aid to obtain the porous magnesium hydroxide loaded with an anti-aging aid, and the solvent of the solution of the anti-aging aid is selected from any one or more of methanol, ethanol, acetone, ethyl acetate, dichloromethane, and N,N-dimethylformamide; More preferably, in the solution of the anti-aging agent, the concentration of the anti-aging agent is 0.18 mol / L to 3.60 mol / L, and the soaking treatment time is 0.5 h to 2 h; More preferably, the porous magnesium hydroxide is immersed in a solution of an anti-aging agent and then dried at 45° C. to 65° C. for 2 h to 6 h to obtain the porous magnesium hydroxide loaded with the anti-aging agent.
9. The method for preparing a photovoltaic adhesive film according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing a base resin and porous magnesium hydroxide loaded with an anti-aging aid according to the composition of a photovoltaic adhesive film to obtain a mixture, and extruding and casting the mixture into a film to obtain the photovoltaic adhesive film; Preferably, the extrusion casting temperature is 90°C to 120°C.
10. A photovoltaic module, characterized in that: The photovoltaic module includes a panel, a first adhesive film, a battery cell, a second adhesive film and a backplane stacked in sequence, the first adhesive film and / or the second adhesive film is the photovoltaic adhesive film described in any one of claims 1 to 7, or the first adhesive film and / or the second adhesive film is a photovoltaic adhesive film prepared by the preparation method described in claim 8 or 9.